A torso model comparison of temperature preservation devices for use in the prehospital environment. Issue 6 (2nd February 2016) - Zasa, Michele; Flowers, Neil; Zideman, David; Hodgetts, Timothy J; Harris, Tim
Abstract : Background: Hypothermia is an independent predictor of increased morbidity and mortality in patients with trauma. Several strategies and products have been developed to minimise patients' heat loss in the prehospital arena, but there is little evidence to inform the clinician concerning their effectiveness. Methods: We used a human torso model consisting of two 5.5-litre fluid bags to simultaneously compare four passive (space blanket, bubble wrap, Blizzard blanket, ambulance blanket) and one active (Ready-Heat II blanket) temperature preservation products. A torso model without any temperature preservation device provided a control. For each test, the torso models were warmed to 37°C and left outdoors. Core temperatures were recorded every 10 min for 1 h in total; tests were repeated 10 times. Results: A significant difference in temperature was detected among groups at 30 and 60 min (F (1.29, 10.30)=103.58, p<0.001 and F (1.64, 14.78)=163.28, p<0.001, respectively). Mean temperature reductions (95% CI) after 1 h of environmental exposure were the following: 11.6 (10.3 to 12.9) °C in control group, 4.5 (3.9 to 5.1) °C in space blanket group, 3.6 (3 to 4.3) °C in bubble-wrap group, 2.1 (1.7 to 2.5) °C in Blizzard blanket group, 6.1 (5.8 to 6.5) °C in ambulance blanket group and 1.1 (0.7 to 1.6) °C in Ready-Heat II blanket group. Conclusions: In this study, using a torso model based on two 5 L dialysate bags we found the Ready-Heat II heating blanket and Blizzard blanket were associated with lower rates of heat loss after 60 min environmental exposure than the other devices tested.